Diversity, distribution, and sustainability of traditional medicinal plants in Kaski district, western Nepal - Khakurel, Dhruba; Uprety, Yadav; Ahn, Gyeongik; Cha, Joon-Yung; Kim, Woe-Yeon; Lee, Sung-Ho; Rajbhandary, Sangeeta (Frontiers in Pharmacology, 2022)
Medicinal plants are the primary source of traditional healthcare systems in many rural areas mostly in developing countries This study aimed to document and analyze the diversity, distribution, and sustainability of the traditional medicinal plants used by the Gurung people of the Sikles region in western Nepal. Ethnobotanical data were collected through focus group discussions and individual interviews, and analyzed using descriptive and inferential statistics. Prior informed consent was obtained before each interview. Quantitative ethnobotanical indices such as informant consensus factor, relative frequency of citation, and use values were also calculated. A possible association among these indices was tested using correlation analysis. A total of 115 wild medicinal plant species belonging to 106 genera and 71 families were documented. Asteraceae and Rosaceae were the dominant families whereas herbs were the most dominant life form. Roots were the most used plant part, paste was the most common method of preparation, and most of the medical formulations were taken orally. The highest number of medicinal plants were used to treat stomach disorders. The average informant consensus value of 0.79 indicates a high consensus among respondents in selecting medicinal plants. Lindera neesiana, Neopicrorhiza scrophulariiflora, Paris polyphylla, and Bergenia ciliata were found to be high-ranking medicinal plants based on the relative frequency of citation and use value. The genders did not affect medicinal plants’ knowledge but age had a significant correlation. Most of the informants agreed that medicinal plants are under pressure due to overharvesting and a lack of proper forest management practices. The number of medicinal plants reported from the study area indicates that the Gurung people possess rich traditional knowledge, and the vegetation of the Sikles region constitutes rich diversity of medicinal plants.